Model Hidrologi Terdistribusi untuk Analisis Debit Terserap pada Sumur Resapan, Lubang Biopori dan Kolam Retensi - Elvi Roza Syofyan; Bambang Istijono -; Amrizal Saidi -; Revalin Herdianto - (Jurnal Ilmiah Poli Rekayasa, 2020)
Infiltration wells, biopore holes, retention ponds serve to collect surface water from rain and then seep into the ground to become ground water reserves. This study aims to look at the application of a distributed hydrological model for the analysis of absorbed discharges in infiltration wells, biopore holes and retention ponds in the Batang Kuranji watershed. Research methods the study was conducted using a survey method that is secondary data collection and primary data. In this study the techniques of rainfall data analysis, Batang Kuranji watershed land use, Runoff analysis using distributed hydrological models and absorbed discharges in infiltration wells, biopore holes, retention ponds in the Batang Kuranji watershed. By applying model 4 using 1 infiltration wells, 2 biopore holes and 4 retention ponds can reduce the runoff rate in the sub-watershed by 7.514% - 27.545%, for the watershed level can reduce the discharge of 15.297%, the more the number of absorption wells, biopori holes and retention ponds more effective in reducing runoff in the Batang Kuranji watershed.